How Effective Monetry Policy Signals Inflation in Indian Economy? - Ganguly, P; Gunwani, R (International Journal of Computer Sciences and Engineering, 2025)
The regulating mechanism of monetary policy plays an important role in the Indian economy as it conveys the central bank’s valuation and its future outlook to the general public. Inflation measurement is fundamental to the conduct of monetary policy. In every country government takes some actions in Economic field that cover the systems for setting Interest Rates & Government Budget as well as labor market, National ownership & many other areas of government interventions into the Economy. Such policies are often influenced by International Institutions like IMF or World Bank as well as political beliefs & consequent policies of parties. This paper concludes all about how monetary policy help to regulate inflation in Indian economy and it also shows how changes are made to hook the instability occurred in recent development of the country due to inflation. In this paper we will also study whether the monetary policy really a helpful technique in signaling Inflation in country like India or not?